Endoscopy is a Resource With Diagnostic/Therapeutic Power - Ríos, Aldebharán Avila; Hernández, José Luis García; Cabello, José de Jesús Urbina; Avila, Juan Antonio Juarez; Suárez, Ivonne Alondra León; Barrón, Gema Méndez; Elizondo, Camila Rivera; Molina, Ratziel Alberto Lezama; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: endoscopy is in a unique position at the interface between various medical and surgical disciplines. Endoscopy is a medical procedure that allows the interior of the entire gastrointestinal tract to be visualized by means of an instrument, among other organs and/or systems of the human body. Objective: To carry out art history based on an exhaustive search of the national and international medical literature on endoscopy in the medical field. Discussion: endoscopic studies have evolved the form of better diagnosis, in prevention, or as a screening, for an early cure, for a timely treatment or, failing that, in a palliation in the prognosis of patients in symptomatologic scenarios, to a degree as specific or even surprising. From procedures where only observation is performed to specialized surgical treatments with effective, decisive techniques and in a multi-application environment. Conclusions: endoscopy is currently a resource that has evolved by leaps and bounds due to abrupt and constant technological progress, allowing its application in such a varied way in the medical and/or surgical field, with the aim of a diagnostic/therapeutic approach, which benefits patients in their health exponentially, facilitates medical work and reduces costs exorbitantly.